2021
DOI: 10.1371/journal.pone.0259848
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing multidimensional poverty in Migori County, Kenya and its association with depression

Abstract: Introduction Narrow, unidimensional measures of poverty often fail to measure true poverty and inadequately capture its drivers. Multidimensional indices of poverty more accurately capture the diversity of poverty. There is little research regarding the association between multidimensional poverty and depression. Methods A cross-sectional survey was administered in five sub-locations in Migori County, Kenya. A total of 4,765 heads of household were surveyed. Multidimensional poverty indices were used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Census data shows that the percentage of Quechuas and Aymaras grows accordingly with the village’s altitude, and poverty also increases with the altitude of the villages (58). Furthermore, previous studies demonstrated an association of poverty with depression (5963), especially when the measure is done with more sensible instruments such as the multidimensional poverty measurement (64). Therefore, the moderation effect of poverty on the relationship between depression and high altitude will be tested in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Census data shows that the percentage of Quechuas and Aymaras grows accordingly with the village’s altitude, and poverty also increases with the altitude of the villages (58). Furthermore, previous studies demonstrated an association of poverty with depression (5963), especially when the measure is done with more sensible instruments such as the multidimensional poverty measurement (64). Therefore, the moderation effect of poverty on the relationship between depression and high altitude will be tested in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…To monitor impact and allow for improvement, a repeated cross-sectional household survey was designed to assess a wide variety of health metrics in both programming and control areas. [14][15][16][17][18] This study aims to use the most recent iteration of this survey to expand our prior mortality work.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Programming includes an innovative community-led health programme that activates community governance structures, professionalises the community health worker (CHW) role, incorporates traditional birth attendants into the healthcare system and supports public health facilities to improve the quality of care. To monitor impact and allow for improvement, a repeated cross-sectional household survey was designed to assess a wide variety of health metrics in both programming and control areas 14–18. This study aims to use the most recent iteration of this survey to expand our prior mortality work.…”
Section: Introductionmentioning
confidence: 99%